2010
DOI: 10.1159/000322476
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Acculturation Gap-Distress Model: An Integrative Review of Research

Abstract: The acculturation gap-distress model purports that immigrant children acculturate to their new culture at a quicker pace than their parents, leading to family conflict and youth maladjustment. This article reviews literature on the acculturation gap-distress model, showing that acculturation gaps function in unique ways depending on many social and contextual variables. In contrast to the original model, which only discusses 1 type of acculturation gap, there are at least 4 types of acculturation gaps: (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
340
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(373 citation statements)
references
References 126 publications
15
340
2
5
Order By: Relevance
“…A larger gap between parents and their adolescent children is often associated with lower levels of adolescent well-being (e.g., Pfafferott & Brown, 2006). Yet, a recent review suggests that effects may differ between different types of gaps (Telzer, 2010).…”
Section: Family-related Conditions For Acculturation and Adjustmentmentioning
confidence: 99%
“…A larger gap between parents and their adolescent children is often associated with lower levels of adolescent well-being (e.g., Pfafferott & Brown, 2006). Yet, a recent review suggests that effects may differ between different types of gaps (Telzer, 2010).…”
Section: Family-related Conditions For Acculturation and Adjustmentmentioning
confidence: 99%
“…For immigrants, however, additional parent-child dynamics have to be considered. We have already indicated that immigrant adolescents seem to adjust to a new context more quickly (Cheung et al 2011), which results in an acculturation gap (Birman 2006;Telzer 2011) and in adolescents' taking over responsibilities. These responsibilities are often related to language brokering activities (Morales and Hanson 2005;Weisskirch 2005), which means that adolescents translate documents, bills, and so forth for their parents (Weisskirch 2005), a behavior that is exhibited by approximately 90% of immigrant adolescents, but with substantial interindividual variation (Jones and Trickett 2005;Morales and Hanson 2005).…”
Section: Interdyadic Differences In Mother-adolescent Agreementmentioning
confidence: 94%
“…A second argument relates to additional differences between mothers and adolescents due to different paces of adaptation (Cheung et al 2011). Usually, adolescents adapt more rapidly than their parents to a new cultural environment, which results in an acculturative gap (Birman 2006;Telzer 2011) and in children taking over family responsibilities, such as translating documents for their parents (language brokering) (Morales and Hanson 2005;Weisskirch 2005), or assuming adult roles (parentification) (Titzmann 2012). This differential adaptation is assumed to bear the risk of intergenerational alienation (Fillmore 2000) or acculturative family distancing (Hwang 2006;Hwang et al 2010).…”
Section: Ethnic Group Differences In Mother-adolescent Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, such approaches have been used to understand the experiences of immigrant and ethnic minority children (Guiberson, 2009;Stodolska, 2008;Telzer, 2011), adolescent peer experiences (Kingery, Erdley, Marshall, Whitaker, & Reuter, 2010), emotional regulation (Chambers, Gullone, & Allen, 2009), sports coaching (McCullick et al, 2009), and family resiliency (Benzies & Mychasiuk, 2009). Integrative reviews have been undertaken to understand trends in topical content and methods, such as Graham and Ismail's (2011) study conducted in the field of community psychology.…”
Section: Literature Reviewmentioning
confidence: 99%